Development and validation of a medication safety self-assessment tool for primary healthcare settings in China - Shang Yong-guang; Qin Wang-jun; Guo Dong-jie; Li Peng-mei; Zhang Lei (Frontiers in Medicine)
BackgroundMedication safety remains a global public health challenge, particularly in resource-constrained primary care settings. This study aimed to develop and validate a specific, proactive, medication safety self-assessment tool tailored for primary healthcare settings in China.MethodsA mixed-methods approach combining literature review, field investigations, a Delphi expert consultation (3 rounds), and Analytic Hierarchy Process (AHP) was implemented. Forty-three voluntarily participating settings completed the self-assessment, with effectiveness validated through correlation analysis between assessment scores and adverse drug events (ADEs) indicators (medication errors, dispensing/prescribing errors).ResultsWe constructed a medication safety self-assessment tool for primary care settings comprising 5 domains, 18 core characteristics, and 84 self-assessment items. The mean percent score for 43 participating primary care settings was 81.5% ± 11.7%, and Spearman’s rank correlations were used to examine the relationship between the overall assessment scores to the incidence of ADEs (Correlation Coefficient is −0.448, p = 0.003).ConclusionAs the first medication safety assessment tool for Chinese primary healthcare settings, based on current medication practices and validated through ADE, implementation demonstrates potential to enhance medication safety practices.